2015
DOI: 10.1080/19440049.2015.1055594
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mercury and cadmium via seafood consumption in Italy: estimated dietary intake (EWI) and target hazard quotient (THQ)

Abstract: Mercury (Hg) and cadmium (Cd) were quantified in fish, cephalopods and crustaceans from Italian supermarkets. Sample compliance with European dietary standards as well as human health risks according to provisional tolerable weekly intake (PTWI) and the methodology of target hazard quotient (THQ) were evaluated. Both element levels were under European legal limits, except for some fish having Hg and Cd contents exceeding or equal to critical values. Estimated weekly intakes (Hg: fish = 0.07-1.44 µg kg(-1) bw w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 27 publications
7
36
1
3
Order By: Relevance
“…The health risk value of mercury in the study area was lower than in other countries and a polluted area in the Gulf of Thailand (Table 3). Although the present calculations were less than 1, the chemical forms of mercury in seafood should be investigated because the toxicity of Hg in organic forms, such as methyl mercury, are the most toxic ones [37]. Moreover, it found that the health risk from metal concentrations in this study area was lower than in polluted areas in the Gulf of Thailand.…”
Section: Health Risk Assessment Of Cadmium and Mercury In Seafoodmentioning
confidence: 59%
“…The health risk value of mercury in the study area was lower than in other countries and a polluted area in the Gulf of Thailand (Table 3). Although the present calculations were less than 1, the chemical forms of mercury in seafood should be investigated because the toxicity of Hg in organic forms, such as methyl mercury, are the most toxic ones [37]. Moreover, it found that the health risk from metal concentrations in this study area was lower than in polluted areas in the Gulf of Thailand.…”
Section: Health Risk Assessment Of Cadmium and Mercury In Seafoodmentioning
confidence: 59%
“…for Pb [27]. In this study Cd and Pb concentrations were higher that levels reported in literature for the Mediterranean basin [28,29] and suggest higher pollution levels for fish resources, this implies that the high consumption of these contaminated resources, especially in Skikda province, could indicate a risk of public health.…”
Section: Mullus Sephaluscontrasting
confidence: 41%
“…However, vegetable consumption was just one part of food consumption. In addition to vegetable consumption, rice [ 18 , 31 ], meat [ 18 , 30 , 45 ], fish [ 29 , 32 ], and tobacco [ 46 ] consumption also led to ingestion of large amounts of heavy metals. For the residents of Shizhuyuan mining area, food consumption, inhalation of soil particles, drinking water, and dermal contact were the important pathways for human exposure to toxic metals [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%